SOSIOLOGI PENEGAKAN HUKUM DALAM KEJAHATAN GENG MOTOR - Fikri Fikri (DIKTUM: Jurnal Syariah dan Hukum, 2012)
We know that the rule of law requires both citizens and governments to be subject to known and standing laws. The enforcement or supremacy of law also requires generality in the law. This principle is a further development of the principle of equality before the law. Laws should not be made in respect of particular persons. Those laws ought not to be too easily changeable. Stable laws are a prerequisite of the certainty and confidence which form an essential part of individual freedom and security. In this connexion, when the Geng of Motorcycle appeared, there are many problems of law in society. They can’t feel their freedom, security and conducive situation. Therefore, we must give a big attention to solve the Geng of Motorcycle, so that in society the laws ought to be rooted in moral principles, which cannot be achieved if they are framed in too detailed a manner. The enforcement of law to the Geng of Motorcycle requires a definition of law to which the above principles may go some way. A failure to maintain the formal differences between these things must lead to a conception of law as nothing more than authorisation for power, rather than the guarantee of liberty, equally to all.The rule of law ensures that individuals have a secure area of autonomy and have settled expectations by having their rights and duties pre-established and enforced by law.